Comparison of Different Chronic Maintenance Antithrombotic Strategies in Patients with Coronary Artery Disease: A Systematic Review and Network Meta-Analysis - Junyan Zhang; Zhongxiu Chen; Yujia Cai; Chen Li; Yong He (Cardiovascular Therapeutics)
Background. Optimal antithrombotic therapy during the chronic maintenance period in patients with coronary artery disease (CAD) is unknown. We compared five kinds of mainstream chronic maintenance antithrombotic strategies at least one year after the acute phase: aspirin alone, clopidogrel alone, ticagrelor alone, continued dual antiplatelet therapy (DAPT) for a period of time, and maintenance with aspirin combined with a low-dose anticoagulant such as rivaroxaban. Methods. Ten randomized, controlled trials were selected using PubMed, Ovid MEDLINE, Embase, and Cochrane library through February 2023. The primary outcome was main adverse cardiac events (MACEs), and secondary outcomes include net adverse clinical events (NACEs), cardiac death, all-cause death, ischemic stroke, stent thrombosis, total bleeding, and major bleeding. A network meta-analysis was conducted with a random-effects model. Data extraction was performed by three independent reviewers. Results. Our search identified ten eligible randomized controlled trials enrolling a total of 82,084 patients comparing different chronic maintenance antithrombotic strategies. As for the primary endpoint, there was no statistical difference in MACE outcomes between any two of the five methods. As for the secondary endpoint, there was no statistical difference in NACE, major bleeding, all-cause death, cardiac death, and stent thrombosis between any two methods. The aspirin plus low-dose rivaroxaban group had a lower incidence of ischemic stroke compared to the aspirin group (OR=0.49, 95% CrI 0.26-0.91). And the prolonged DAPT group had a higher total bleeding rate compared to aspirin group (OR=2.4, 95% CrI 1.1-5.9). Conclusions. In terms of MACE, NACE, all-cause death, cardiac death, stent thrombosis, and major bleeding, there were no significant differences between using aspirin alone, clopidogrel alone, and ticagrelor alone; extending DAPT duration; and using aspirin combined with low-dose rivaroxaban for chronic maintenance antithrombotic regimens. However, choosing aspirin combined with low-dose rivaroxaban can reduce the incidence of ischemic stroke, and prolonged DAPT may have a higher rate of total bleeding. However, it is important to note that this study is based on indirect comparisons, and there is currently a lack of direct evidence comparing various maintenance antiplatelet therapy regimens. Further high-quality studies are needed to address this gap and provide more conclusive evidence on the comparative effectiveness of different maintenance antiplatelet strategies.